Impact of General Anesthesia on Safety and Outcomes in the Endovascular Arm of Interventional Management of Stroke (IMS) III Trial. Issue 8 (August 2015) - Abou-Chebl, Alex; Yeatts, Sharon D.; Yan, Bernard; Cockroft, Kevin; Goyal, Mayank; Jovin, Tudor; Khatri, Pooja; Meyers, Phillip; Spilker, Judith; Sugg, Rebecca; Wartenberg, Katja E.; Tomsick, Tom; et al.
Abstract : Background and Purpose—: General anesthesia (GA) for endovascular therapy (EVT) of acute ischemic stroke may be associated with worse outcomes. Methods—: The Interventional Management of Stroke III trial randomized patients within 3 hours of acute ischemic stroke onset to intravenous tissue-type plasminogen activator±EVT. GA use within 7 hours of stroke onset was recorded per protocol. Good outcome was defined as 90-day modified Rankin Scale ⩽2. A multivariable analysis adjusting for dichotomized National Institutes of Health Stroke Scale (NIHSS; 8–19 versus ≥20), age, and time from onset to groin puncture was performed. Results—: Four hundred thirty-four patients were randomized to EVT, 269 (62%) were treated under local anesthesia and 147 (33.9%) under GA; 18 (4%) were undetermined. The 2 groups were comparable except for median baseline NIHSS (16 local anesthesia versus 18 GA; P <0.0001). The GA group was less likely to achieve a good outcome (adjusted relative risk, 0.68; confidence interval, 0.52–0.90; P =0.0056) and had increased in-hospital mortality (adjusted relative risk, 2.84; confidence interval, 1.65–4.91; P =0.0002). Those with medically indicated GA had worse outcomes (adjusted relative risk, 0.49; confidence interval, 0.30–0.81; P =0.005) and increased mortality (relative risk, 3.93; confidence interval, 2.18–7.10; P <0.0001) with a trend for higher mortality with routine GA. There was no significant difference in the adjusted risks of subarachnoid hemorrhage ( P =0.32) or symptomatic intracerebral hemorrhage ( P =0.37). Conclusions—: GA was associated with worse neurological outcomes and increased mortality in the EVT arm; this was primarily true among patients with medical indications for GA. Relative risk estimates, though not statistically significant, suggest reduced risk for subarachnoid hemorrhage and symptomatic intracerebral hemorrhage under local anesthesia. Although the reasons for these associations are not clear, these data support the use of local anesthesia when possible during EVT. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00359424. Abstract : Supplemental Digital Content is available in the text.